2013
DOI: 10.1016/j.apradiso.2013.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive waste management: Review on clearance levels and acceptance criteria legislation, requirements and standards

Abstract: In 2011 the joint research project Metrology for Radioactive Waste Management (MetroRWM)(1) of the European Metrology Research Programme (EMRP) started with a total duration of three years. Within this project, new metrological resources for the assessment of radioactive waste, including their calibration with new reference materials traceable to national standards will be developed. This paper gives a review on national, European and international strategies as basis for science-based metrological requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The obtained results can be explained by taking into account that the threshold energy of the reactions (γ,n) is 8.5 MeV for heavy cores (i.e., for Pb, W, etc.) and about 10 MeV for most of the isotopes of lower atomic number present in the materials 33 . In this case, the energy of the dismantled LINAC was 6 MeV, so, despite the time elapsed, no activation has occurred in the concrete materials in the bunker.…”
Section: Analysis Of Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The obtained results can be explained by taking into account that the threshold energy of the reactions (γ,n) is 8.5 MeV for heavy cores (i.e., for Pb, W, etc.) and about 10 MeV for most of the isotopes of lower atomic number present in the materials 33 . In this case, the energy of the dismantled LINAC was 6 MeV, so, despite the time elapsed, no activation has occurred in the concrete materials in the bunker.…”
Section: Analysis Of Resultsmentioning
confidence: 84%
“…In the measurements of equivalent dose rates (μSv/h H10; Table 5), at a given distance from the surface, all values did not exceed the legal limit of 2 μSv/h 33 …”
Section: Analysis Of Resultsmentioning
confidence: 90%
“…Nuclear energy is a high-efficiency energy source with high energy density, low cost, and no air pollution emission [1]. However, the nuclear facilities of nuclear power, medicine, scientific research, industry, and agriculture can generate large amounts of nuclear waste during operation and decommissioning [2,3]. Nuclear waste contains more than 30 radioactive elements, mainly including actinides (such as Pu and U), fission elements (such as Cs, Sr, I, Xe, and Ru), and other radioactive elements, which can emit radioactive alpha rays (α-rays), beta rays (β-rays), and gamma rays (c-rays) during the decay of the nucleus, and X-rays by atomic shell electron transitions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, actual nuclear wastes could not be used in these studies due to their radioactive, corrosive, and other harmful properties to the human body. In addition, it is unpractical to study the radiation damage to the solidified bodies for hundreds of years or even thousands of years through actual experiments [2,24]. Researchers [24][25][26][27] found that some nonradioactive isotopes of the radionuclides or some other nonradioactive elements had similar physical and chemical properties to the corresponding radionuclides.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are coming to the end of their operating lives and will require decommissioning. After decommissioning a nuclear reactor, long-lived radioisotopes formed by (n,γ) reaction in biological concrete shielding cause difficulty in waste management of the activated shielding [1,2]. Therefore, decommissioning of nuclear installations after their operating life-time and their dismantling are connected with the necessity of the disassembling, handling and disposing of a large amount of radioactive equipment and structures.…”
Section: Introductionmentioning
confidence: 99%